2005
DOI: 10.1007/s00520-005-0892-6
|View full text |Cite
|
Sign up to set email alerts
|

Is there a correlation between spirituality and anxiety and depression in patients with advanced cancer?

Abstract: This study found a significant negative correlation between spirituality (in particular, the existential aspect) and anxiety and depression in patients with advanced cancer. Religious well-being and strength of belief had no impact on psychological well-being in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
85
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(105 citation statements)
references
References 44 publications
(93 reference statements)
15
85
0
5
Order By: Relevance
“…The (2015) were in line with the present study (31)(32)(33)(34). However, Hojjati et al (2010) have stated that the majority of hemodialysis patients in their study were highly spiritual and had religious affiliation (35).…”
Section: Discussionsupporting
confidence: 88%
“…The (2015) were in line with the present study (31)(32)(33)(34). However, Hojjati et al (2010) have stated that the majority of hemodialysis patients in their study were highly spiritual and had religious affiliation (35).…”
Section: Discussionsupporting
confidence: 88%
“…An intriguing theme for future research is to unravel which aspects of spirituality are most important in coping with a stressful event, such as cancer. To date, only the subdivision into the horizontal dimension (i.e., a feeling of meaning, peace, and connectedness to the self and others) and into the vertical dimension (i.e., the belief in and experience of connectedness with a higher power) has been explored, showing the horizontal dimension to appear more closely related to well-being than the vertical dimension (Krupski et al, 2006;Laubmeier, Zakowski, & Bair, 2004;McCoubrie & Davies, 2006;Zavala, Maliski, Kwan, Fink, & Litwin, 2008). Our new questionnaire can be used to determine which aspects of the horizontal dimension (i.e., meaningfulness, trust, acceptance, caring for others, or connectedness with nature) are most supportive in dealing with stressful events, such as cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that, for women with chronic illnesses, spirituality is associated with psychological well-being and assists with coping with their illnesses (Gioiella, Berkman, & Robinson, 1998;Martin & Sachse, 2002;Reynolds, 2006;Simoni, Martone, & Kerwin, 2002). In addition, higher levels of spirituality are associated with lower levels of depression, anxiety, and stress (Boscaglia, Clarke, Jobling, & Quinn, 2005;Jesse & Reed, 2004;McCoubrie & Davies, 2006). Yet, regardless of health status, older women consistently report higher levels of spirituality than their younger counterparts (Gioiella et al;Humphreys, 2000;Martin & Sachse;Romero et al, 2006).…”
mentioning
confidence: 99%